A New Insight of Herbal Promises Against Ocular Disorders: An Occuloinformatics Approach - Srivastava, Prachi; Tiwari, Anshul (Current Topics in Medicinal Chemistry, 2016)
Ocular biology is a prominent area of research and advancement, as eyes are the most precious for us to see this beautiful world. Though we have overcome many ocular problems, but still challenges, no doubt exist in the path of the journey. Many ocular disorders still either have surgery or symptomatic drugs as a treatment. If we could get a better preventive way or single drug with many and more potential effects, will definitely be a boon for our society. Keeping the way we tried to focus on the impending effects of phytochemicals on some important ocular disorders. Our study promised with virtual screening based on important insilico protocols that can be a landmark for better futuristic approach towards novel drug development. As a selection Eales’ Disease, Diabetic Retinopathy, Uveitis, Age related Macular Disorder, CRVO were taken. Causative Protein identification is the basic of study and further advance Insilico approaches were based on this target in respective disorders. Retinol Binding protein-3 and Retinal S antigen protein in case of Eales, Erythropoietin in the case of Diabetic Retinopathy, Nucleotide-binding oligomerization domain-containing protein-2 in case of Uveitis, Hemicentin-1 in case of Age related Macular Disorder, Coagulation Factor-V in case of CRVO were identified. Insilico characterization, Secondary and Tertiary structure prediction makes the study more prominent towards virtual screening. Virtual Screening was based on the parameters of docking, which reflects the potentiality of Ginkgolide, D-pinitol, Gugglesterones, Berberine and Curcumin herbal molecules against above mentioned ocular disorders respectively. Study signifies about the spectacular vision of herbal uses just to limit the vast side effects of synthetic chemicals used as ocular drugs.
Keywords: Tertiary structure